Dear Evan Hansen the novel - Emmich, Val; Levenson, Steven 1984-; Pasek, Benj 1985-; Paul, Justin 1985- (Little, Brown and Company, 2018)
Evan goes from being a nobody to everyone's hero and a social media superstar after a chance encounter with Connor just before his suicide leads others to believe Evan was his only friend
"Poppy."
Keywords: Popularity; High schools; Schools; Social media; Suicide; Social Media; Suizid; High school; Beliebtheit; Jugendbuch